Analisis Efektivitas Kebijakan UMKM dalam Mendorong Ekonomi Kreatif di Era Digital - Erinaldi; Ade Rindi Ely; Dita Sofia; Riska Ayu Fitri (PT. Hasba Edukasi Mandiri, 2025)
Digital transformation serves as a key factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in today’s increasingly competitive digital economy. The Indonesian government has implemented various strategic policies to accelerate MSME digitalization, including digital literacy training programs, financial incentives, and the strengthening of technological infrastructure. Moreover, the application of the creative economy concept expands business opportunities through innovation based on creativity, local culture, and modern technology. This study aims to analyze the effectiveness of government policies in supporting the digitalization process and to examine the role of the creative economy in improving MSME competitiveness in Indonesia. The research employs a qualitative approach with a descriptive- analytical design through literature studies and in-depth interviews with MSME actors and relevant stakeholders. The results indicate that digitalization and the creative economy significantly contribute to expanding market access, increasing operational efficiency, and fostering innovation capability among MSMEs. However, challenges such as low digital literacy, limited financial capital, a lack of adaptive human resources, and unequal infrastructure distribution remain major obstacles in the digital transformation process. Therefore, stronger collaboration among the government, business actors, the private sector, and educational institutions is essential to build an inclusive, innovative, and sustainable digital economy ecosystem.